Rethinking social corporate responsibility: a case in Argentina from the point of view of the civil society - Guidi, Marta (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
On the basis of a concrete case, the negotiation about compensation and reparation on environmental damage in an Indio-Community in Northern Argentinien, this Paper focuses on the relationship between state, business and civil society and on its expressions in everyday reality. The paper looks at the way extractive industry impacts on people and on the environment. It reflects on the growing ascendancy of business on governmental and multilateral circles. And it looks to the way CSR has evolved lately in order to rethink on it feasibility and threats.